Barrier-removal plans and pedestrian infrastructure equity for people with disabilities. (August 2022) - Eisenberg, Yochai; Hofstra, Amy; Berquist, Sierra; Gould, Robert; Jones, Robin
Abstract: Despite decades of civil rights legislation for Americans with disabilities, much of the pedestrian infrastructure in cities remains inaccessible. This inaccessibility has led to numerous lawsuits in major US cities. Some communities are proactively planning more equitable pedestrian infrastructure by developing barrier removal plans that can facilitate active transportation. However, limited research has explored the relationship between plans and more equitable pedestrian infrastructure. In this study, we leveraged Google Earth's Street View and aerial imagery to evaluate whether having a barrier removal plan was associated with more accessible pedestrian infrastructure. We found that accessibility scores were higher for communities with plans compared to those without. We found no relationship between higher quality plans and better accessibility scores. Our results suggest that barrier-removal planning may support more equitable pedestrian infrastructure. These findings can inform state and federal policies on enforcement of existing laws and training/resource needs.